Recomendações de acessibilidade e usabilidade para desenvolvimento de projetos de interface de software para pessoas com paralisia cerebral - SANTOS, Thiago Sales (2019)
This research project has as main objectives: to evaluate software designed for people with Cerebral Palsy checking some problems which hinder or prevent the access and the interaction with this software; presenting assistive technologies that facilitate the access for people with Cerebral Palsy, with the goal of developing a educational software’s prototype available for web access as main content the legends of the Amazon (Interface Design). Also proposing some recommendations for accessibility and usability for people with Cerebral Palsy, based on assessments and observations made during the development of this project. The results of these evaluations served as the fundamental basis for construction of a good interface design, thus achieving the expected results for the research.